Study of the reclamation state of the rocky chestnut lands of the Republic of Armenia and ways of improving - Eloyan, A. Sh.; Jhangiryan, T. A.; Barseghyan, M. H. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Improvement and effective use of unused land in conditions of land poor of the Republic of Armenia is one of the crucial problems in the field of agriculture. The purpose of the work has been to study the reclamation condition of the uncultivated chestnut lands of the Republic of Armenia and recommend a system of measures to improve them for involvement in agricultural turnover. The chemical and physical properties of the lands have been studied, as well as the degree of rockiness, and the content of nutrients. It has been shown that the lands are characterized by medium and firm rockiness, the presence of cemented horizons, weak and medium clayloam mechanical composition, and medium and firm calcareousness. Land reclamation measures have been proposed, which will allow the establishment of perennial plantings on the territory ՀՀ սակավահողության պայմաններում անօգտագործելի հողերի բարելավումը և արդյունավետ օգտագործումը գյուղատնտեսության ոլորտի կարևոր հիմնախնդիրներից են: Աշխատանքի նպատակն է եղել ուսումնասիրել ՀՀ չմշակվող շագանակագույն քարքարոտ հողերի մելիորատիվ վիճակը և առաջարկել դրանց բարելավման միջոցառումների համակարգ՝ գյուղատնտեսական շրջանառության մեջ ներգրավելու համար: Հետազոտվել են հողերի քիմիական և ֆիզիկական հատկությունները, քարքարոտության աստիճանը, սննդատարրերի պարունակությունը: Ցույց է տրվել, որ հողերը բնութագրվում են միջին և ուժեղ քարքարոտությամբ, ցեմենտացած հորիզոնների առկայությամբ, թույլ և միջին կավավազային մեխանիկական կազմով, միջին և ուժեղ կարբոնատությամբ: Առաջարկվել են հողերի բարելավման մելիորատիվ միջոցառումներ, որոնք թույլ կտան տարածքում հիմնել բազմամյա տնկարկներ: Улучшение и эффективное использование неиспользуемых земель в условиях малоземелья Республики Армения является одной из важнейших проблем в области сельского хозяйства. Целью работы было изучить мелиоративное состояние необрабатываемых каштановых земель Республики Армения и рекомендовать систему мер по их улучшению для вовлечения в сельскохозяйственный оборот. Были изучены химические и физические свойства почв, а также степень каменистости и содержание питательных веществ. Было показано, что земли характеризуются средней и твердой каменистостью, наличием сцементированных горизонтов, слабым и средним глинисто-суглинистым механическим составом, а также средней и сильной карбонатностью. Были предложены мелиоративные мероприятия, которые позволят создать на территории многолетние насаждения.
Keywords: Agriculture